Effect of PCBM impregnation on titanium dioxide films containing Poly(3-alkylthiophene) derivatives - Mayara Masae Kubota; Paulo Rogério Catarini da Silva; Henrique de Santana (Results in Surfaces and Interfaces)
To study how the presence of [6,6]-phenyl-C₆₁-butyric acid methyl ester (PCBM) affects interactions and electronic transfer between poly(3-alkylthiophenes) (P3ATs) and titanium dioxide (TiO2), which are priority effects in the active layer of inverted organic solar cells, PCBM was first incorporated into the ITO/TiO2 system and then the poly(3-methylthiophene) or poly(3-hexylthiophene) films were electrochemically deposited. The interfaces formed were called ITO/TiO2/PCBM/P3ATs, subsequently characterized by Raman spectroscopy. The presence of PCBM was found to destabilize the radical cation segments of P3ATs, favoring the dication segments and interfering with the strong interaction observed between P3ATs and TiO2 studied in a previous work. The possibility of interaction between PCBM and TiO2 was also studied using the X-ray Diffraction technique, but demonstrated the non-interference of PCBM in the crystalline structure of TiO2. These results were supplemented by Confocal Raman images, presenting areas of higher and lower concentrations of PCBM, TiO2 and P3ATs. However, even with these areas, the spectra demonstrated a certain homogeneity of the segments studied throughout the generated film.